Financial frictions, real estate collateral, and small firm activity in Europe - Ryan N. Banerjee; Kristian Blickle (Federal Reserve Bank of New York, 2018)
We observe significant heterogeneity in the correlation between changes in house prices and the growth of small firms across certain countries in Europe. We find that, overall, the correlation is far greater in Southern Europe than in Northern Europe. Using a simple model, we show that this heterogeneity may relate to financial frictions in a country. We confirm the model's propositions in a number of empirical analyses for the following countries in Northern and Southern Europe: the United Kingdom, Norway, France, Italy, Spain, and Portugal. Small firms in countries with higher financial frictions (for example, places where bankruptcy resolution is more difficult and/or takes longer) see a greater dependence on "stable" real estate collateral. This is most pronounced for opaque (for example, very young) firms. Through an extension to our model and our choice of specification, we show that our findings are most consistent with a collateral-value-based credit supply channel and rule out a consumer-driven demand effect.
Keywords: G30; G33; K11; O47; R30; 330; firm financing; real estate collateral; credit supply; bankruptcy laws; financial frictions